Pengaruh Kesadaran Wajib Pajak Dan Pelayanan Fiskus Terhadap Penerimaan Pajak Bumi Dan Bangunan Pedesaan Dan Perkotaan (PBB-P2) Di Kabupaten Buleleng - Komang Aryadi Saputra; I Nyoman Putra Yasa (Universitas Pendidikan Ganesha, 2022)
This study aims to determine the effect of taxpayer awareness and tax services on rural and urban land and building tax revenue (PBB-P2). This study uses a quantitative approach using instruments in its measurement and statistical processing. This research was conducted in Buleleng Regency with a population of 238,000 rural and urban land and building taxpayers (PBB-P2). Sampling using purposive sampling in order to obtain a sample of 265 taxpayers. The research data were collected using a questionnaire which was then processed with multiple linear regression analysis with the help of SPSS version 22.The results of the study stated that (1) taxpayer awareness (X1) had a positive and significant effect on PBB-P2 revenue and (2) tax authorities (X2) has a positive and significant effect on PBB-P2 revenue. Abstract This study aims to determine the effect of taxpayer awareness and tax services on rural and urban land and building tax revenue (PBB-P2). This study uses a quantitative approach using instruments in its measurement and statistical processing. This research was conducted in Buleleng Regency with a population of 238,000 rural and urban land and building taxpayers (PBB-P2). Sampling using purposive sampling in order to obtain a sample of 265 taxpayers. The research data were collected using a questionnaire which was then processed with multiple linear regression analysis with the help of SPSS version 22.The results of the study stated that (1) taxpayer awareness (X1) had a positive and significant effect on PBB-P2 revenue and (2) tax authorities (X2) has a positive and significant effect on PBB-P2 revenue.